2019
DOI: 10.29252/beat-070405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Titatnium Dioxide Nanoparticles/Gelatin Composite on Infected Skin Wound Healing; An Animal Model Study

Abstract: Objective:To evaluate effects of titanium dioxide /gelatin nanocomposite on wound healing in mice as a model study. Methods:Fifty male rats were randomized into five groups of ten animals each. In group I, 0.1 mL sterile saline 0.9% solution was added to the wounds with no infection. In group II, the wounds were infected with MRSA and only treated with 0.1 mL the sterile saline 0.9% solution. In group III, infected wounds were treated with gelatin. In group IV, animals with infected wounds were treated with 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 25 publications
2
18
1
1
Order By: Relevance
“…47 Recently many studies reported that the wound dressing with TDN enhanced wound healing due to its antimicrobial and cell growth stimulation features. [48][49][50][51][52] In contrast to our findings, Kotlhao et al (2017) reported that TDN had no antibacterial activity against Pseudomonas aeruginosa 53 which may be due to the reduction in porosity of Gram-negative cell wall or existence of efflux pump that causes a decrease in intracellular concentrations of these compounds, resulting in a drastic reduction of biocidal activity. 54 The Effect of TDN and Antibiotics on MDR P. aeruginosa Isolates…”
Section: Susceptibility Of P Aeruginosa Isolates To Tdncontrasting
confidence: 94%
“…47 Recently many studies reported that the wound dressing with TDN enhanced wound healing due to its antimicrobial and cell growth stimulation features. [48][49][50][51][52] In contrast to our findings, Kotlhao et al (2017) reported that TDN had no antibacterial activity against Pseudomonas aeruginosa 53 which may be due to the reduction in porosity of Gram-negative cell wall or existence of efflux pump that causes a decrease in intracellular concentrations of these compounds, resulting in a drastic reduction of biocidal activity. 54 The Effect of TDN and Antibiotics on MDR P. aeruginosa Isolates…”
Section: Susceptibility Of P Aeruginosa Isolates To Tdncontrasting
confidence: 94%
“…Similarly, native gelatin showed good adhesion to fibroblasts and cell viability from 72 h up to 7 days [ 93 , 94 ]. The in vivo studies done by Hsu et al, (2019) [ 95 ], Nikpasand et al, (2019) [ 96 ], and Jang et al, (2017) [ 97 ] indicated the formation of thick granulation tissues, increased re-epithelization and blood vessel formation with an absence of cytotoxic effects confirmed through CCK-8 assays. For both Col and gelatin scaffolds, the analysed physicochemical properties correlated with those of an ideal scaffold for wound healing as per discussed in the physicochemical section above.…”
Section: Collagen and Gelatin For Skin Wound Healingmentioning
confidence: 99%
“…Observa-se grande número de estudos desenvolvidos em modelos experimentais 12,13 . No entanto, esses modelos utilizados para avaliação do tratamento de feridas não contemplam, em sua totalidade, os princípios da cobertura ideal.…”
Section: Discussionunclassified